Innovative trends in personalized software engineering and information systems the case of intelligent and adaptive e-learning systems - Troussas, Christos; Sgouropoulou, Cleo (Amsterdam : IOS Press, 2020)
Intro -- Title Page -- Foreword -- Contents -- Chapter 1: Introduction -- Chapter 2: Intelligent Knowledge-Based Approaches for Adaptive and Personalized Learning Technology Systems -- Chapter 3: Comparison of Techniques and Good Practices for Adaptive and Personalized Learning Technology Systems -- Chapter 4: Evaluation Methods of Intelligent Knowledge-Based Learning Technology Systems -- Chapter 5: Conclusions -- References.
Includes bibliographical references.
Keywords: Distance education; Educational technology -- Planning; Artificial intelligence -- Educational applications